Molecular allelokaryotyping of pediatric acute lymphoblastic leukemias by high-resolution single nucleotide polymorphism oligonucleotide genomic microarray - Kawamata, Norihiko (American Society of Hematology, 2008)
Pediatric acute lymphoblastic leukemia (ALL) is a malignant disease resulting from accumulation of genetic alterations. A robust technology, single nucleotide polymorphism oligonucleotide genomic microarray (SNP-chip) in concert with bioinformatics offers the opportunity to discover the genetic lesions associated with ALL. We examined 399 pediatric ALL samples and their matched remission marrows at 50 000/250 000 SNP sites using an SNP-chip platform. Correlations between genetic abnormalities and clinical features were examined. Three common genetic alterations were found: deletion of ETV6, deletion of p16INK4A, and hyperdiploidy, as well as a number of novel recurrent genetic alterations. Uniparental disomy (UPD) was a frequent event, especially affecting chromosome 9. A cohort of children with hyperdiploid ALL without gain of chromosomes 17 and 18 had a poor prognosis. Molecular allelokaryotyping is a robust tool to define small genetic abnormalities including UPD, which is usually overlooked by standard methods. This technique was able to detect subgroups with a poor prognosis based on their genetic status.